Journey to the north of India overland from England, through Russia, Persia, and Affghaunistaun - Conolly, Arthur, 1807-1842. (London)
2 cilt (1. c. viii, 350, 30 sayfa, [1] sayfa resim, [1] katlı harita ; 2. c. 358, [2] sayfa, [1] sayfa resim)